2008
DOI: 10.3390/s8127882
|View full text |Cite
|
Sign up to set email alerts
|

Problems Encountered in Fluctuating Flame Temperature Measurements by Thermocouple

Abstract: Some thermocouple experiments were carried out in order to obtain sensitivity of thermocouple readings to fluctuations in flames and to determine if the average thermocouple reading was representative of the local volume temperature for fluctuating flames. The thermocouples considered were an exposed junction thermocouple and a fully sheathed thermocouple with comparable time constants. Either the voltage signal or indicated temperature for each test was recorded at sampling rates between 300-4,096 Hz. The tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…These are due to the temperature and the velocity dependences of the TC time constant. A study [29] emphasised the ability of the 250-lm-diameter thermocouple to capture the flame pulsations up to a rate of 10 Hz. This means that the effective time constant of the TC in flames is lower than 0.1 s. Furthermore, when using thermocouples in flames, some errors may be due to the radiative heat losses.…”
Section: Fuelmentioning
confidence: 99%
“…These are due to the temperature and the velocity dependences of the TC time constant. A study [29] emphasised the ability of the 250-lm-diameter thermocouple to capture the flame pulsations up to a rate of 10 Hz. This means that the effective time constant of the TC in flames is lower than 0.1 s. Furthermore, when using thermocouples in flames, some errors may be due to the radiative heat losses.…”
Section: Fuelmentioning
confidence: 99%
“…During the burning process, a large amount of energy is released and distributed unevenly. In the flame there are also radiation losses, temperature field distortions and thermocouple inertia [3,4]. Additional sources of measurement accuracy are present in the flame: soot, liquid drops, solid crystals particles etc.…”
Section: Introductionmentioning
confidence: 99%
“…Because of their multiple advantages of low cost, robustness and easily standardization, thermocouples are the most frequently used sensors for temperature measurement. They can measure a wide range of temperatures and have long-term stability and high reliability [ 3 , 4 ]. However, the major problems of this sensor for signals conditioning are the cold junction compensation and linearization of the transfer relationship between temperature and output voltage [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because these calibration equations are higher order polynomial equations, Sarma and Boruan [ 6 ] suggested that the whole temperature range can be divided into smaller ranges, with lower degree polynomial calibrations being used for each range [ 4 ], but the literature contains no reports of any applications of this method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation